Art principles and their application to living rooms - Starck, Helen Ruth, author; Williamson, Maude, advisor; Heilig, Herb, committee member; Kozak, Andrew, committee member (Colorado State University. Libraries, 1946)
To view the abstract, please see the full text of the document.
List of Tables (page 6) appears between pages 22-23.
Keywords: Interior decoration